2022
DOI: 10.1111/jocd.14830
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic outcomes of one‐minute application of sodium hydroxide versus phenol in the chemical cauterization of ingrown toenails

Abstract: Background Ingrown nails are frequently encountered in dermatology practice. The recurrence tendency of the disorder makes chemical cauterization essential during surgical procedures. In studies comparing nail matrix cauterization with sodium hydroxide (NaOH) versus phenol, phenol's application time was highly variable. Objective To compare the therapeutic outcomes of matrix cauterization for a standard duration of one minute for NaOH versus phenol in stage II and III ingrown nails. Material and methods The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Surgical techniques of ingrown toenails involve removal of the affected side of the nail and matricectomy, often with phenol, 16 sodium hydroxide 17 or wedge resection 18 but may have certain disadvantages, such as prolonged wound healing or infection, 19 restriction of everyday activities, scars, or deformations. Various authors have reported that patients prefer conservative treatments over invasive surgical procedures 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical techniques of ingrown toenails involve removal of the affected side of the nail and matricectomy, often with phenol, 16 sodium hydroxide 17 or wedge resection 18 but may have certain disadvantages, such as prolonged wound healing or infection, 19 restriction of everyday activities, scars, or deformations. Various authors have reported that patients prefer conservative treatments over invasive surgical procedures 20–22 .…”
Section: Discussionmentioning
confidence: 99%